The Geometric Evaluation of Jalan Majalengka-Cikijing West Java - Dini Widyanti; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2024)
Highways are one of the land transportation accesses that support human movement in driving and sending goods from one region to another. The geometric of the road is the highway building above the ground level both vertically and horizontally with the assumption that the ground surface is not flat. Horizontal alignment is often referred to as road situation or road alignment. Corners are where the horizontal alignment is most important. A transverse slope at a bend called superelevation counteracts the centrifugal force the automobile experiences as it makes the turn. The quantitative method can also be interpreted as a research method that looks at reality, symptoms, and phenomena that can be classified, are comparatively constant, tangible, measurable, and observable, and there is a causal link between the symptoms. This study's road evaluation used a 60 km/h design speed and 3.5 m of road width. Using the contour data obtained, road evaluation was carried out using AutCAD® Civil 3D. Based on the calculation results above, the Majalengka-Cikijing road is a hill road type. Then, for the horizontal alignment with a speed of 60 km/hour, the results obtained from 11 horizontal alignments all belong to the Spiral-Cirle-Spiral alignment type.